PENGAPLIKASIAN MODEL PENYELESAIAN MASALAH POLYA DALAM TOPIK PENGATURCARAAN KOMPUTER - Moi, Chin Siew (Proceeding 7th International Seminar on Regional Education, 2015)
Abstract Computer programming and problem solving strategy instruction, when used together may provide an effective means of teaching transferable problem solving skills. The students need to understand how to interpret the given problem before they can represent the correct solution and effectively use specific tools or techniques. A problem solving model have been introduced in this study. This paper reports and discusses the findings collected from the observation of computer science students and the results of their assignments on problem solving statement in a matriculation college. The result shows that there are improvement of problem solving skills among computer science students with the problem solving model applied. Recommendations are given for further investigation into a more effective problem solving model as an alternative in the teaching of computer programming courses and it is expected that the human resources developed to meet the characteristics required by the challenging environment in the 21st centuryKeywords: computer programming, problem solving, computer science